Head louse egg and nit remover—a modern “Quest for the Holy Grail” - Elizabeth R. Brunton; Ian P. Whelan; Rebecca French; Mark N. Burgess; Ian F. Burgess (PeerJ, 2019)
Background The eggs of head lice are fixed to the hair of their hosts by means of a persistent glue-like fixative that is not chemically bound to the substrate. Eggshells stuck to hairs after successfully treating the infestation are a cosmetic issue and a source of misunderstanding about whether the infestation is eliminated. Hitherto, no effective treatment to loosen louse eggs and nits has been found. Methods An extensive screening of surface active compounds, oils, esters, and other cosmetic lubricants used a slip-peel device to measure the forces required to release the grip of the fixative. Promisingly effective compounds were formulated into suitable carriers for further testing. The most effective combination formulation was tested, as a commercial product (Hedrin Stubborn Egg Loosening Lotion), in a usage study of 15 children with nits, in which one half of the head was combed only on damp hair and the other half combed after a 10 min treatment using the product. Results Laboratory tests of the forces required to remove nits found that pelagonic acid derivatives, particularly isononyl isononanoate, in the presence of a polymeric gelling agent and water, were most effective to reduce the initial grip of the fixative as well as reducing friction as the eggshell is drawn along the hair shaft and that the final product was significantly (p < 0.05) more effective than several other marketed materials. In the usage study significantly (p = 0.01046) more louse eggs and nits were removed after treatment with the gel. Discussion The product developed through this study is the first with a demonstrable efficacy for loosening the grip of the louse egg fixative from hair. Consequently, until now, and despite the availability of effective pediculicidal treatments, dealing with the eggshells persisting after an infestation has been an onerous task for most households. This type of product can enable families to deal more easily with persistent eggshells and improve self-esteem in affected children.